Migrant Capital as a Resource for Migrant Communities - Saksela-Bergholm, Sanna (Social Inclusion, 2019)
This thematic issue explores the processes and dynamics involved in how different forms of migrant capital are employed and how these relate to processes of social inclusion. Leaning on a Bourdieusian approach, we wish to move beyond existing descriptive studies and theorise the role migration plays in the accumulation, conversion and utilisation of various forms of capital by migrant communities and their members. The articles demonstrate how migrant capital can function as a resource created by migrants during the migration process, or as an outcome of it, and are potentially available to their family members. The articles illustrate via case studies from different national contexts how transnational migrants or members of migrant communities create, accumulate and employ diverse forms of capital in their efforts to achieve inclusion in destination and sending societies.